The association between academic stress and test anxiety in college students: The mediating role of regulatory emotional self-efficacy and the moderating role of parental expectations - Zheng, Guo; Zhang, Qiongzhi; Ran, Guangming (Frontiers in Psychology, 2023)
Academic stress has been showed to be an important factor associated with test anxiety. However, the internal mechanism between them is still not clear. The purpose of this study was to explore whether the relationship between academic stress and test anxiety was affected by parental expectations and regulatory emotional self-efficacy. This study recruited 1,315 volunteers aged 17-25 to complete self-reports on academic stress, parental expectations, regulatory emotional self-efficacy and test anxiety. The results showed that there was a significant positive correlation between academic stress and test anxiety. Additionally, parental expectations were negatively correlated with academic stress but positively correlated with regulatory emotional self-efficacy, and regulatory emotional self-efficacy was negatively correlated with academic stress and test anxiety. The results showed that regulatory emotional self-efficacy played a mediating role in academic stress and test anxiety, and the relationship between academic stress and regulatory emotional self-efficacy was moderated by parental expectations, which indicated that parental expectations and regulatory emotional self-efficacy may play an important role in the relationship between academic stress and test anxiety.